Wireless technology in disease management and medicine. - Clifford, G; Clifton, D (2012)
Healthcare information, and to some extent patient management, is progressing toward a wireless digital future. This change is driven partly by a desire to improve the current state of medicine using new technologies, partly by supply-and-demand economics, and partly by the utility of wireless devices. Wired technology can be cumbersome for patient monitoring and can restrict the behavior of the monitored patients, introducing bias or artifacts. However, wireless technologies, while mitigating some of these issues, have introduced new problems such as data dropout and "information overload" for the clinical team. This review provides an overview of current wireless technology used for patient monitoring and disease management. We identify some of the major related issues and describe some existing and possible solutions. In particular, we discuss the rapidly evolving fields of telemedicine and mHealth in the context of increasingly resource-constrained healthcare systems.